Original paperEvaluation of selected skin barrier functions in atopic dermatitis in relation to the disease severity and pruritus - Polańska, Adriana; Dańczak-Pazdrowska, Aleksandra; Silny, Wojciech; Jenerowicz, Dorota; Osmola-Mańkowska, Agnieszka; Olek-Hrab, Karolina (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: Atopic dermatitis (AD) is an inflammatory pruritic dermatosis, which is characterized by an impaired skin barrier function manifested as an increased transepidermal water loss (TEWL). Aim: Presentation results of instrumental evaluation of the skin barrier function in AD patients in relation to the disease severity as well as pruritus. Material and methods: Fifty-five AD patients aged from 8 to 60 years were enrolled to the study. Epidermal barrier function (TEWL measurement and corneometry) as well as erythema measurement were determined in each patient within the same affected skin region, antecubital fossa. Clinical evaluation was performed using the W-AZS scoring system. Results: There was a statistically significant difference in the mean TEWL values between groups of patients with different degrees of skin inflammation expressed by the W-AZS index, while no significant differences were observed in relation to the skin hydration and ertyhema measurement. There was a statistically significant correlation between the W-AZS index and TEWL as well as between the W-AZS I index and TEWL. Conclusions : Selected parameters of the skin barrier function (TEWL, skin hydration) and the level of erythema are useful in evaluation of AD. Transepidermal water loss measurement presents a good correlation with W-AZS and with intensity of patients itching. Instrumental assessment provides us with a fast and objective evaluation of the eczema status, what seems to be very important in the era of evidence-based medicine.